Sotataito ja poikkitieteellisyyden vaade - Mälkki, Juha (Tiede ja ase, 2017)
The concept of art of war cannot be placed to one specific scientific discipline, because the art of war is, by its nature, an interdisciplinary issue and phenomenon. Hence, an interdisciplinary discourse and interpretations are needed to ensure that current and emerging conflicts can be properly understood in order to enhance the process of building a realistic apparatus to understand the security challenges we face. is article presents a typology for the art of war. e typology illuminates all aspects and approaches needed to understand the nature of art of war comprehensively. In the article, the art of war is described as a phenomenon consisting of human and social factors. Conflicts are products of human interaction and their nature is based on the dynamic reciprocity and of humans, groups, societies, and naturally on the specific regional aspects of the conflict, with its specific characteristics.